(1)ln(5)=f(1)

Simple and best practice solution for (1)ln(5)=f(1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1)ln(5)=f(1) equation:


Simplifying
(1) * ln(5) = f(1)

Reorder the terms for easier multiplication:
1 * 5ln = f(1)

Multiply 1 * 5
5ln = f(1)

Reorder the terms for easier multiplication:
5ln = 1f

Solving
5ln = 1f

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '5n'.
l = 0.2fn-1

Simplifying
l = 0.2fn-1

See similar equations:

| -4-8b=-2(3b-1)-2 | | 4(x^3)-2x=0 | | 9x+6y-5x-11y+7y= | | k-4=12 | | 5t=-750 | | -2y+1=6y | | 2(3x-1)+3(3y-y-x)= | | 3(c-11)=12 | | -2y+0=6y | | (4x-10)(-2)= | | 140=3x+8x+8 | | 5a+7=3a+39 | | 6w-10+-18w= | | 2(30)+8= | | 4+8=36 | | 1-(1/2)(-x+5)=2+3(1-x) | | 15-4x=32 | | 7x-5(2x+2)=-19 | | -14p=156 | | 5+5y-5y=5 | | 17+x=3+17 | | -2(x-8)=6(x+4)-8 | | 5x+8-7x-12= | | y=2x^2+36x+168 | | 5y+6x-3y-5x+4x= | | 5y+6x-3y-5y+4x= | | 15m-9=21 | | -2(x-8)=(6x+4)-8 | | 3.45x+2.5y=52 | | 2r-5=1r | | -2x(x-8)=(6x+4)-8 | | -6r-10s+8r+4s-6= |

Equations solver categories